Synthesis and Chemistry of Bis-imidazole Derivatives: A Review (Global Journal of Science Frontier Research, 2018)
Imidazole, an important heterocycle, having biological and therapeutic properties prompted various medicinal chemists to develop various synthetic methods to synthesize a large number of novel derivatives used in chemotherapy. This fascinating group of heterocyclic compounds has interesting biological activities such as antimicrobial, anticancer, antiviral, analgesic, anti-inflammatory, anthelmintic, anticonvulsant, antiulcer, and anti-allergic activity. Various bis-imidazole derivatives introduced a great contribution not only in the field of synthetic organic chemistry but also in the field of medicinal chemistry and chemotherapy. This article aims to review the work reported in the synthesis and chemistry of bis-imidazole derivatives during past years.
Keywords: imidazole; heterocycle; bis-imidazole